2019
DOI: 10.3389/fimmu.2019.02221
|View full text |Cite
|
Sign up to set email alerts
|

CD27+CD38hi B Cell Frequency During Remission Predicts Relapsing Disease in Granulomatosis With Polyangiitis Patients

Abstract: Background: Granulomatosis with polyangiitis (GPA) patients are prone to disease relapses. We aimed to determine whether GPA patients at risk for relapse can be identified by differences in B cell subset frequencies.Methods: Eighty-five GPA patients were monitored for a median period of 3.1 years (range: 0.1–6.3). Circulating B cell subset frequencies were analyzed by flow cytometry determining the expression of CD19, CD38, and CD27. B cell subset frequencies at the time of inclusion of future-relapsing (F-R) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 37 publications
(46 reference statements)
8
27
0
Order By: Relevance
“…The ANCA test is useful in monitoring patients with persistently elevated ANCA, as those with a reappearance of ANCA or an increase in ANCA levels have an increased likelihood of relapse, although restarting or intensifying therapy based on ANCA alone is not recommended. This aligns with an association between earlier relapse and a higher frequency of memory B cells 163 , while a higher plasmablast percentage during remission is also predictive of relapse 164 . The acute-phase markers C-reactive protein and erythrocyte sedimentation rate are of limited use in evaluating disease activity due to their lack of specificity.…”
Section: Biomarkerssupporting
confidence: 81%
“…The ANCA test is useful in monitoring patients with persistently elevated ANCA, as those with a reappearance of ANCA or an increase in ANCA levels have an increased likelihood of relapse, although restarting or intensifying therapy based on ANCA alone is not recommended. This aligns with an association between earlier relapse and a higher frequency of memory B cells 163 , while a higher plasmablast percentage during remission is also predictive of relapse 164 . The acute-phase markers C-reactive protein and erythrocyte sedimentation rate are of limited use in evaluating disease activity due to their lack of specificity.…”
Section: Biomarkerssupporting
confidence: 81%
“…Although B cell count and ANCA titer increase are shown to be associated with relapse [35,36], these are not recommended for monitoring treatment [3]. Von Borstel et al have reported CD27 + CD38 hi B cell frequencies during remission were associated with the risk for relapse in GPA patients, suggesting more specific cell subsets may potentially be markers associated with disease relapse [37]. We showed that changes in plasma cells were strongly correlated with the reactivation of CNS disease.…”
Section: Discussionmentioning
confidence: 71%
“…Persistent positive-ANCAs (22), CD27-CD38hi B-cell frequency (23) and non-standardized glucocorticoid therapy are key risk factors for a poor prognosis. Although endobronchial involvement may improve symptoms, further studies are required to investigate whether the incomplete excision of the lesion can cause a relapse of the existing granulomata development (24).…”
Section: Discussionmentioning
confidence: 99%